The Invisible Barrier to Safe Textile Recycling - Sharkey, Martin; Coggins, Marie (Frontiers in Sustainability, 2022)
• Presence of certain chemical additives (e.g. halogenated flame retardants, perfluoroalkyl substances, and phthalates) could hinder textile recycling operations as their presence renders end-of-life materials as “hazardous” and therefore not recyclable; • In 2018, there was an estimated minimum of 1.7 million tonnes of hazardous and unrecyclable textile waste generated in the EU; • Blanket-bans on classes of chemicals would be likely partially effective in reducing environmental uptake of and human exposure to harmful chemicals, but could also lead to increased use of “regrettable substitutions” with unforeseen implications; • Legislative restrictions on chemicals must be accompanied with reduction in demand: reducing volume of textile waste generated by reducing volume consumed, thus eliminating necessity for huge volume of chemical additives in the first instance.